Pengetahuan, Sikap dan Tindakan Ibu dalam Pola Makan Anak Penderita Autis di Yayasan Tali Kasih - Aritonang, Evawany; Ervika, Eka (Jurnal Kedokteran Indonesia, 2009)
Background: One of the disorders found in autistic children is immune system aberration that affects gluten and casein metabolism, food intolerance, and vulnerability to infection e. Improved dietary pattern may help cure autism and reduce brain and digestion dysfunction. This study aimed to describe knowledge, attitude, and practice in dietary pattern among mothers with autistic children at Tali Kasih Foundation.Methods: This was a descriptive study. Population in this research is amount to 32 mothers then become total sampling. Data collected by using interview technique then analyzed descriptively in frequency distribution table.Results: The results showed that 31.3% of mothers with autistic children had good knowledge and 68.8% had fair knowledge. All of mothers had good attitude. 62.5% of mothers had good practice, and 37.5% had fair practice.Conclusion: Most of mothers of autistic children at Tali Kasih Foundation have either good or fair knowledge, attitude, and practice in feeding pattern. Jurnal Kedokteran Indonesia: 1 (1): 102-107Key words: Knowledge, attitude, practice, mothers with autistic children, dietary pattern.